KERALA'S GULF CONNECTION : Emigration, Remittances and their Macroeconomic Impact 1972-2000 - Kannan, KP and Hari, KS (Centre for Development Studies-WP328, 2002)
This paper attempts to construct a time series estimation of remittances from abroad to the Kerala economy for the period 1972 to 2000. It is now widely acknowledged that foreign remittances in the economy of the State of Kerala in India in the form of money sent by its workers in the Gulf countries play a crucial role. The study finds that by the early nineties remittances to the Kerala economy assumed a significant share of state income. This ranged from 17 percent during 1991-92 and 24 percent during 1997-98 with an average of 22 percent for the second half of the nineties. The liberalisation of the Indian economic policies, particularly the foreign exchange rate, benefited Kerala directly. Adding the remittance income to the Net State Domestic Product, a Modified State Income series has been constructed. As a result Kerala's per capita income not only caught up with the average per capita income for India but started exceeding it reaching 49 percent above the national average by the end of the nineties. This tallies with per capita consumer expenditure in Kerala, which was in excess of 41 percent above the national average by the end of the nineties. Remittances have also made significant impact on savings. By the nineties savings rates in the Kerala economy seem to have reached such high levels comparable to the East and South East Asian countries. The significance of remittances can also be gauged by its relative magnitudes. By the end of the nineties remittances reached such levels that they were well above the total government expenditure, value added in manufacturing and even the value added in industrial sector as a whole.